UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VII B SMP NEGERI 2 SALATIGA PADA MATERI PENYAJIAN DATA MELALUI MODEL PROBLEM BASED LEARNING (PBL) - Fitria Nurul Azizah; Mahmudi Mahmudi; Kristinawati Kristinawati; Helti Lygia Mampouw (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to enhance students' problem-solving skills and learning outcomes on data presentation and interpretation in the form of pie charts and measures of the center of the data in the single data. This research is a collaborative classroom action research (PTKK). The study employs the Problem-Based Learning (PBL) model, conducted at SMP Negeri 2 Salatiga in class VII B with 32 students. The results indicate an improvement in students' problem-solving abilities for each indicator. In cycle I, the student's ability to understand the problem was 36.2 %, which increased by 42.2 % to 78.4 % in cycle II. Furthermore, students' making a plan skill in cycle I was 51.2 %, increasing by 26.9 % to 78.1 % in cycle II. The student's ability to execute the plan increased by 19.6 % from 55.7 % in cycle I to 75.3 % in cycle II. The student's ability to look back and reflect in cycle I was 42.2 %, and in cycle II, it was 75 %, an increase of 32.8 %. The study also showed an improvement in learning outcomes. In cycle I, the classical student mastery level was 40.6 %, with an average learning outcome of 67.2. In contrast, in cycle II, the classical student mastery level was 75 %, with an average learning outcome of 78.2. In this case, the classical student mastery level increased by 34.4 %, with an average student learning outcome increase of 11. Based on these results, the Problem-Based Learning (PBL) model can enhance students' problem-solving abilities